Screening songs in Hispanic and Lusophone cinema - Shaw, L. (Lisa); Stone, Robert (Manchester University Press, 2019)
In this volume, eighteen experts from a variety of academic backgrounds explore the use of songs in films from the Spanish- and Portuguese-speaking worlds. This volume illustrates how - rather than simply helping to tell the story of - songs in Hispanic and Lusophone cinema commonly upset the hierarchy of the visual over the aural, thereby rendering their hearing a complex and rich subject for analysis.Screening songs. constitutes a ground-breaking, interdisciplinary collection. Of particular interest to scholars and academics in the areas of Film Studies, Hispanic Studies, Lusophone Studies and Musicology, this volume opens up the study of Hispanic and Lusophone cinema to vital, new, critical approaches. The soundtracks of films as varied as City of God, All About My Mother, Bad Education and Buena Vista Social Club are analysed alongside those of lesser-known works that range from the melodramas of Mexican cinema's golden age to Brazilian and Portuguese musical comedies from the 1940s and 1950s. Fiction films are studied alongside documentaries, the work of established directors like Pedro Almodóvar, Carlos Saura and Nelson Pereira dos Santos alongside that of emerging filmmakers, and performances by iconic stars like Caetano Veloso and Chavela Vargas alongside the songs of Spanish Gypsy groups, Mexican folk songs and contemporary Brazilian rap.
1. Singing of dubious desire: Imperio Argentina and Penélope Cruz as Nazi Germany's exotic Other 2. Voicing gender: transgender performance and the national imaginary in the Spanish cinema of the democratic era3. Bien pagá: popular song in the films of Pedro Almodóvar 4. El otro lado de la cama: remixed Transition (1973-1982) 5. On the function of punk aesthetics in Salto al vacío and Historias del Kronen 6. Soundscapes of resistance in the quinqui film 7. Song-shaped cinema: the performance of Gypsy and Basque songs in relation to film form 8. Travelling song: music, iteration and translation in La leyenda del tiempo 9. Sound moves: immigration and music in Cosas que dejé en La Habana 10. The Afro-Cuban soundscape of Mexico City: authenticating spaces of violence and immorality in Salón México and Víctimas del pecado 11. Blues traveller: Habana blues and the framing of diasporic cubanía 12. Dancing in the dark: Saura's Tango 13. Re-making Frida Kahlo through song in Frida14. 'Silence! Fado is about to be sung': fado and the comédia à portuguesa 15. Sounds from Brazil: brasilidade and the rise of the music documentary 16. Soundtrack to roguery: music and malandragem in the city 17. The Brazilian chanchada's musical moments and the performance of identity 18. Orpheus in Babylon: music, myth and realism in the films of Rio de Janeiro Index.
Keywords: Motion picture music -- Spain -- History and criticism.; Motion picture music -- Portugal -- History and criticism.; Motion pictures -- Spain -- History.; Motion pictures -- Portugal -- History.; Film, Musique de -- Espagne -- Histoire et critique.; Film, Musique de -- Portugal -- Histoire et critique.; Cinéma -- Espagne -- Histoire.; Cinéma -- Portugal -- Histoire.; Music.; MUSIC / General.; Motion picture music.; Motion pictures.; Portugal.; Spain.; Criticism, interpretation, etc.; History.